Організація наукової діяльності в університетах Наддніпрянської України в дореформений період - Пилипенко, О. (Сiверянський літопис, 2021)
Метою статті є здійснення ретроспективного аналізу процесу зародження, розвитку та організації наукової діяльності в перших університетах на українських землях Російської імперії в першій половині ХІХ ст. Робота здійснена з використанням порівняльно-історичного методу дослідження. Науковою новизною дослідження є запровадження до наукового обігу нових джерел та фактичного матеріалу, які до сьогодні залишалися поза увагою вітчизняних дослідників. Їх обнародування дозволить по-новому підійти до розв’язання багатьох історичних проблем. Висновки: на розвиток науки в Наддніпрянській Україні в дореформену добу XIX ст. впливали принципові політичні й соціально-економічні протиріччя того часу. Зародження капіталістичних форм господарювання потребувало широкого вивчення, дослідження й використання природних багатств, поступу наукового прогресу. Але, з іншого боку, намагання пануючої політичної еліти будь-що зберегти феодально-кріпосничі підвалини суттєво перешкоджали розвитку науково-дослідної діяльності. Недостатня кількість кваліфікованих наукових кадрів, хронічне недофінансування й слабка матеріальна база університетів суттєво заважали масштабному проведенню наукових досліджень. У цих умовах науку розвивали ентузіасти. Українські вчені брали активну участь у створенні й діяльності наукових товариств. Науково-дослідна робота членів цих установ була орієнтована на задоволення практичних потреб промисловості, сільського господарства, охорони здоров’я, розвитку освітнього рівня населення. Розвиток української науки, удосконалення форм її організації відбувався нерівномірно, переживаючи періоди спаду й піднесення. Аналіз державних заходів щодо керівництва наукою, системи підготовки вчених, удосконалення форм наукової діяльності засвідчує, що вирішення цих важливих проблем перебувало в тісному зв’язку із зовнішньою і внутрішньою політикою царського уряду. Але, попри складні умови, прогрес української науки був неухильним і постійним. Вона почала набирати силу, зростала кількість учених, відбувався процес перетворення науки в національну за своїм складом, що сприяло зародженню, формуванню та становленню вітчизняних наукових шкіл та їх подальшому розвитку. The purpose of the article is realization of retrospective analysis of process of origin, development and organization of academic activity in the first universities on Ukrainian territory of the Russian empire in the first half of ХІХ century. Methodologically work is carried out with the usage of historic-comparative method of research. The scientific novelty of this study is introduction to scientific circulation some new sources and factual materials, that remained out of Ukrainian researchers’ attention, which allowed to find a new approaches to the identified tasks. Conclusions. Thus, the first half of XIX century is an important period in history of Ukrainian science. So, there was founded system of research centers, that in future evolved steadily. In this period organizational forms of native science got further development on Ukrainian territory. Scientific centers equaled on providing universities in the leading countries of Western Europe. Development of science on territory of Naddniprianska Ukraine is constrained, first of all, with the origin of the Kharkiv and Kyiv universities. Empire’s government contributed to this move under the the influence of European tendencies. The origin of capitalist relations and industry needed new scientific and technological inventions and developments. Without science development it could not be modernization processes in economy of the state. Ukrainian science was conceived in extremely unfavorable conditions. On development of native prоfеssоrs’ research work in universities different factors negative influenced, such as absence of research infrastructure, insufficient funding etc. On development of science in Naddniprianska Ukraine in pre-reform time of XIX century fundamental political and socio-economic contradictions influenced greatly. The origin of capitalist forms of manage needed a wide study, research and usage of natural riches, advancement of science development. But, on the other hand, attempt of dominating political elite to save anything middle ages foundations substantially prevented to development of research activity. The insufficient amount of qualified scientific personnel, chronic moneyless and weak material base of universities, substantially interfered with scale realization of scientific researches. In these conditions native science was developed by enthusiasts. The Ukrainian scientists participated actively in creation and activity of scientific communities. Research work of members of these establishments was oriented to satisfaction of practical necessities of industry, agriculture, health protection, development of educational level of population. Development of Ukrainian science, perfect forms of its organization took place unevenly, experiencing the periods of slump and presentation. Analysis of state politic in relation to guidance by science, the system of preparation of qualified scientific personnel, perfection of forms of scientific activity certifies that a decision of these important problems was in close connection with the foreign and internal policy of empire’s government. But, in spite of difficult terms, progress of Ukrainian science was steady and permanent. Native science began to collect force, the amount of scientists grew, there was a process of transformation of science in national after the composition, that assisted an origin, forming and becoming of native scientific schools and then to further development of Ukrainian science at all.